2016
DOI: 10.1017/s0022215116008082
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes towards external auditory canal exostosis and its preventability in surfers in the UK: cross-sectional study

Abstract: The findings suggest that a significant minority of UK surfers have no knowledge about this condition. Knowledge of external auditory canal exostosis was significantly associated with earplug use when surfing. Efforts to improve surfers' knowledge are required to enable surfers to better protect themselves, which could reduce the incidence of external auditory canal exostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…In a study conducted in the UK investigating awareness and attitudes of surfers towards EAE,13 it was reported that the majority of the participants (66.6%) believed that the condition was inevitable, a result similar to what was found in our study. Additionally, many surfers in the previous study similarly reported that earplugs reduced balance and limited their surfing performance.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted in the UK investigating awareness and attitudes of surfers towards EAE,13 it was reported that the majority of the participants (66.6%) believed that the condition was inevitable, a result similar to what was found in our study. Additionally, many surfers in the previous study similarly reported that earplugs reduced balance and limited their surfing performance.…”
Section: Discussionsupporting
confidence: 89%
“…Surfers started to wear earplugs after the first symptoms appeared. Morris and al demonstrated that knowledge of EAE was significantly associated with earplug use when surfing (21).…”
Section: Applicability Of Findingsmentioning
confidence: 99%
“…There is probably a geographical tendency to develop these lesions; if one lives in a coastal region, one may be more likely to surf or to be exposed to the conditions which encourage exostoses to develop. Indeed, this appears to be reflected in the populations examined in the literature [4] , [9] , [10] , [11] , [12] , [13] . It is difficult to ascertain the true age and gender prevalence of EAC exostoses given that anyone can participate in aquatic sports such as cold-water surfing.…”
Section: Discussionmentioning
confidence: 97%